Scaled design of PEF treatment reactors for electroporation-assisted extraction processes. (October 2016) - Sack, Martin; Mueller, Georg
Abstract: In industrial applications electroporation-assisted extraction processes are about to replace conventional extraction. The devices for PEF treatment are designed specifically to the needs of each application. However, the design process of the electrode system and field geometry inside a PEF treatment reactor consists in general of similar steps to scale from laboratory-scale experiments done in batches up to a large-scale device operating continuously. Thereby, the electrode system might be tailored specifically to an application. In contrast to a closed PEF treatment reactor for batch processing with homogeneous electric field distribution an open electrode system with inlet and outlet section involves additional losses due to inhomogeneities of the electric field geometry. The article describes a novel approach to scale up an electrode design and to define for it an optimum operating voltage with respect to high energy efficiency in a straight-forward design process based on scaling laws. Moreover, a new method is presented to derive an efficiency factor for any given electrode geometry. It is based on a comparison of the specific power required for operating the electrode system under investigation inside a PEF treatment reactor to the specific power for a cubical PEF treatment chamber with homogeneous field distribution. Examples are given based on the design of a PEF treatment reactor for crushed grapes. Industrial relevance: PEF treatment devices for electroporation-assisted extraction are becoming increasingly interesting for industrial applications due to the benefits they offer with respect to product quality and energy savings. Challenges when transferring pulse parameters as obtained from laboratory scale experiments to industrial scale devices arise from electric field inhomogeneities in PEF treatment reactors designed for continuous flow. This work therefore presents a novel method to evaluate the electric field distribution inside the PEF treatment reactor with respect to energy efficiency. The derived scaling laws enable an energy-efficient up-scaling of any given electrode profile towards large scale for products such as sugar beets, potatoes, apples or crushed grapes in a straight-forward design process. Highlights: Straight-forward design process of PEF treatment reactors for continuous flow Novel method for energy-efficient up-scaling of an electrode geometry Comparison of electrode designs with respect to energy efficiency